Guide to Ideas on Drug Abuse Programs and Policies - Gordon, Paula, Comp.; Committee for Psychedelic Drug Information, Berkeley, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
The "GUIDE" was conceived as a way of accelerating the process of finding and working out viable approaches to solving the drug abuse problem. Policy changes are suggested which would recognize the necessity of medical and educational interventions. The wide variety of material, which was compiled, included: (1) summaries of currently operating drug abuse programs; (2) ideas concerning the use of media in drug abuse education efforts; (3) the utilization of former drug users in drug abuse programs; (4) tips on counseling techniques; (5) a summary and budget for a high school drug abuse counseling program; and (6) an outline of an M.A. curriculum for drug abuse education. (TL)
Availability: Committee for Psychedelic Drug Information, P. O. Box 851, Berkeley, California 94701 ($2.50 per copy).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Antisocial Behavior; Counseling Effectiveness; Counseling; Curriculum Design; Drug Addiction; Health; Curriculum Development; Drug Abuse; Drug Legislation; Health Education; Program Development